Environmental Communication Publications in Indonesia’s Leading Communication Journals. A Systematic Review - Mira Rochyadi-Reetz; Jens Wolling (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
As an emerging country, Indonesia is facing many environmental problems, with some of the most critical being plastic waste, severe deforestation, and climate change. Under such conditions, communication science plays an important role in pointing to the best way to inform the public so as to stimulate engagement and action to solve these problems. In this article, a systematic literature review of papers on environmental communication published in three leading communication journals in Indonesia was conducted. The findings show that despite the severe environmental problems in Indonesia, a limited number of studies on environmental communication have been published, and only a few methods and designs have been used. Therefore, more attention from communication scholars and intellectuals in Indonesia is needed to address environmental problems in their research. Creating an environmental communication division in existing communication associations is proposed as a practical solution, among others, and is discussed in the outlook section of this study